Physiological studies on the effect of Myrtus communis extract on the blood serum in rats - Al-Zail, Noura I.; Aboalhaj , Abdusalam M.; El-Gharbawy, Saad M. S. (Al-Mukhtar Journal of Sciences, 2008)
The aim of this study was to test the effect of the ethanolic extract of Myrtus communis leaves on the blood serum in white rats. The animals were given a dose of 2 g/kg orally. 37 rats were divided in to 3 groups. The first group was given the dose daily for 7 days and the second one was treated for 14 days. In the third group some animals were given the dose for 7 days and some for 14 days for the purpose of studying the blood proteins profile using electrophoresis. Each group included some animals as a control. The animals which were treated with the extract showed bleeding through mouth and nose and were lethargic and tired and lost apetite. Furthermore, the weight of these animals was significantly lower than those in the controls. Biochemical analysis showed significant reduction in the level of glucose in the blood, while there was significant increase in the level of total serum protein, serum albumin, the concentration of sodium and potassium ions .Gel electrophoresis showed an increase in the number of protein bands as well as the appearance of new protein bands with high molecular weights in the treated animals in comparison with the control.